Psychological Resilience and Its Relationship with Rumor Perception in Electronic Social Media Among Women in Al-Madinah Al-Munawwarah - Al-Mohammadi, Amal Atiyat Allah (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the relationship between psychological resilience and rumor perception in electronic social media among a sample of women in Al-Madinah Al-Monawara. It sought to examine their level of rumor perception and the extent to which rumors in social media impact their psychological resilience. To achieve the study's objectives, the descriptive correlational approach was adopted, utilizing the Psychological Resilience Scale and the Rumor Perception Scale on a sample of 200 women from Al-Madinah Al-Monawara. The findings indicated a high level of overall psychological resilience among the women in Al-Madinah Al-Monawara. Their community exhibits unique characteristics that distinguish it from others in studies related to resilience and rumor perception. The study also revealed a high level of rumor perception among the participants, along with a heightened sense of social responsibility and awareness of their surrounding environment and its influences. Moreover, they demonstrated an ability to mitigate the negative effects of rumors in electronic social media. A strong and confirmed correlation was found between psychological resilience and rumor perception. Additionally, all age groups of women showed similar high levels of rumor perception, indicating that age does not significantly impact psychological resilience. Similarly, educational level did not influence their rumor perception or psychological resilience. The study recommends emphasizing psychological resilience and raising awareness about avoiding rumors on electronic social media. Furthermore, it calls for conducting more research on rumors in electronic social media.
Keywords: Psychological Resilience; Rumor Perception; Al-Madinah Al-Monawara; Women